Cruce de miradas sobre Lepa Vida (Hermosa Vida) - Pregelj, Barbara (Ars et humanitas, 2015)
"Lepa Vida" (Fair Vida) is one of the most common motifs in Slovenian literature. The motif is from a folk song with many variants which in the course of time, and with each new author's view, assumed further layers. So far there have been 43 literary variations on the Fair Vida motif recorded since 1932, as well as many instances of arrangements for children and youth. In this paper I present the main characteristics of the motif in folk literature, in France Prešeren ("Od Lepe Vide"; "Of the Fair Vida"), and in Andrej Rozman Roza Lepa Vida v akciji (Fair Vida in Action), that is, the source/original, the canonical, and the subversive. I initially present the findings about the origins of the motif, the sociological-historical background against which it came into being, as well as comparative elements of intercultural and chronotope views and the image of the Other. In the light of comparisons with other Slovenian myths (especially King Matjaž, Martin Krpan, and Peter Klepec) I present the (often rather restrictive) view of literary criticism which frequently reduces the Fair Vida motif to the motif of longing, one of the most common motifs in Slovenian literature. I contrast this with more modern interpretative views that take into account both feminist theory and analysis of the discourse of power as it derives from the repeated (subversive, parodic) reading of the motif which Andrej Rozman Roza presents in Lepa Vida v akciji.
Keywords: Cankar, Ivan; Hrastelj, Stanka; kanon; Lepa Vida; ljudski motivi; miti; mythology; Prešeren, France; Rozman, Andrej; Slovene literature; slovenska književnost; subverzija